1979
DOI: 10.1002/jrs.1250080502
|View full text |Cite
|
Sign up to set email alerts
|

Raman and infrared study on the effects of dimethylsulphoxide (DMSO) on water structure

Abstract: Raman and infrared spectra of liquid dimethylsulphoxide (DMSO) and DMSO-water mixtures in a wide range of concentrations are reported and discussed. It is found that changes in the vibrational spectra can be related to a gradual insertion of water molecules in the cluster structure of liquid DMSO. In the more dilute aqueous solutions a gradual lowering of the vsz0 stretching frequency is observed and this can be related to the cooperative character of DMSO-water interactions. The interpretation of the spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 38 publications
3
58
0
3
Order By: Relevance
“…4 -14 The prevailing view is that most of these effects are associated with DMSO's strong hydrophilic nature, which leads to the formation of stoichiometrically well-defined DMSO-water aggregates, with the concomitant formation of a hydrogen bond network and pronounced structural microheterogeneities. 10,[15][16][17][18] No evidence of hydrophobic association between DMSO molecules, as suggested by early experiments, 19,20 has been found by neutron diffraction analyses. 17 More recently, DMSO-water systems have been studied by experimental techniques such as time-resolved Kerr spectroscopy, 21 quasi-elastic neutron scattering, 22,23 timeresolved fluorescence upconversion spectroscopy, 23 and mass spectrometry, 24 devised to investigate molecular clustering.…”
Section: Introductionmentioning
confidence: 90%
“…4 -14 The prevailing view is that most of these effects are associated with DMSO's strong hydrophilic nature, which leads to the formation of stoichiometrically well-defined DMSO-water aggregates, with the concomitant formation of a hydrogen bond network and pronounced structural microheterogeneities. 10,[15][16][17][18] No evidence of hydrophobic association between DMSO molecules, as suggested by early experiments, 19,20 has been found by neutron diffraction analyses. 17 More recently, DMSO-water systems have been studied by experimental techniques such as time-resolved Kerr spectroscopy, 21 quasi-elastic neutron scattering, 22,23 timeresolved fluorescence upconversion spectroscopy, 23 and mass spectrometry, 24 devised to investigate molecular clustering.…”
Section: Introductionmentioning
confidence: 90%
“…The stretching vibration of S_O (1055 cm −1 ) [45] in DMSO was split into two new absorption bands at 1028 cm −1 and 1055 cm −1 . The former could be assigned to the interaction of S_O with hydroxyl in TEG, while the latter to the free S_O groups or S_O groups forming cyclic dimmer with another DMSO molecule [46]. Although FTIR results showed that there were hydrogen bonding between the intramolecular molecules of TEG, the interaction of hydroxyl hydrogen in TEG with oxygen in DMSO was much stronger, which was similar to that between DMSO and methanol [47].…”
Section: Ftir Spectramentioning
confidence: 60%
“…55 For pure DMSO, a broad band peaked at 1043 cm -1 is observed for the SdO stretch mode. 26 The asymmetric band shape ranges from 1000 to 1100 cm -1 and has a shoulder at ∼1055 cm -1 . This broad shape of SdO stretch shows the existence of different aggregates in pure DMSO.…”
Section: Resultsmentioning
confidence: 99%